Impact of post-conflict on public planning (2016)
After fifty years of war along with useless dialogues with The Revolutionary Armed Forces of Colombia (FARC) the peace process was initiated in La Habana, Cuba, on November 12th, 2012; this process was led by Colombian government officials accompanied by FARC representatives with the purpose of ending the conflict in which Colombia has been involved. On the other hand, a list of agreements were the result of diverse political meetings; those will be approved through a plebiscite, Colombians will vote “yes” or “no” in order to guarantee the end of the conflict. However, it will be major challenge for the government in general. All in all, the Colombian government will be responsible of carrying out different mechanisms along with medium and long term strategies to be able to enhance and overcome the social, political and economical difficulties that the country will be dealing in the future.